Proceso de atención de enfermería en preescolar con osteomielitis crónica de peroné derecho. - Castro Barzola, Rosalía Betzaida (2022)
Chronic osteomyelitis is the infection of bone tissue, produced by germs (bacteria or fungi), and is characterized by its destruction or loss. This case study is based on the development of the nursing care process in a preschool patient with a medical diagnostic of chronic osteomyelitis of the right fibula, at the “Hospital de Especialidades Fuerzas Armadas N° 1” in Quito, Ecuador. Imaging studies performed on the patient determined the extent of involvement of the disease. For this reason, was determined that the most favorable treatment to apply in the patient was exeresis of the fibula and the use of antibiotics. The objective of this treatment was to prevent the progress of the infection. The preschooler remained hospitalized for 23 days, during which time appropriate interventions were established to manage his illness and restore his health. At the end of his hospital stay, was possible to evaluate the clinical evolution of the preschooler and the effectiveness of the nursing interventions provided.